Structural diversification in artificial forest stands. Results of experiment plots in eastern Andalusia - Carreras Egaña, C. (Forest Systems, 2006)
Results of experiments of diversification of stands of Pinus halepensis Mill. are presented, sixteen years after the plots installation. In the plots strip cuts of differents widths were made in order to begin natural regeneration, and shrub and tree species were introduced by sowing and planting. Differences in survival and growth of the introduced species and the natural regeneration, in relation to canopy gaps dimensions are shown. Sowings below gaps with widths less than one fourth of the stand height turned out to be useless. Gap widths greater than one third of the stand height have permitted acceptable growth of some of the introduced species, a few of them, e.g. Coronilla juncea L, are begining to regenerate. Planted seedlings have presented high percentajes of mortality and very low growth. Viable regeneration of Pinus halepensis has been limited to gaps with diameter greater than stand height. Analogous results obtained in plots on Pinus pinaster stands are also referred.